Dimension of Drought and Food Security in India. - Singh, A.P., Haffis, Shaik and Reddy, Y.V.R (2007)
The frequent occurrence of drought in the Asian continent, especially in India, challenges food security and agricultural sustainability even after the region has achieved an impressive growth in the productivity and bio-diversity of agricultural crops. Drought is a natural phenomenon that has disastrous consequences and is considered relatively a dangerous event for the living entities. The present paper attempts to provide an insight into the drought years for the two centuries since 1801. It refers to the drought prone districts in India identified under the Drought Prone Area and Desert Development programmes, besides estimating a linear model to analyse food insecurity in particular drought years